Teaching integrative and complementary practices: an analysis of Dentistry courses in Brazil (Research, Society and Development, 2022)
This study aims to evaluate the offer of disciplines related to the teaching of integrative and complementary practices (PICS) in Dentistry courses in Brazil. A cross-sectional, quantitative and exploratory research was carried out, using data provided by the e-MEC Registry, of the Ministry of Education, from January to March 2021. All Higher Education Institutions in active situation were consulted, with official e-mail address, available curriculum matrix or Pedagogical Project of the Course. After applying the inclusion and exclusion criteria, 228 courses were selected to verify the administrative category of the university, the location of the course and the inclusion of subjects related to the teaching of PICS which, when identified, were evaluated for their nature and total workload . The collected data were tabulated and treated descriptively. Considering courses with a complete curriculum available, only 10 (4.39%) offered subjects related to teaching PICS, while the majority of the sample was absent from the curriculum (218; 95.61%). The North, Central-West (1; 10%), Northeast (2; 20%), Southeast (6; 60%) and South (1; 10%) regions had courses offering the subject, of a mandatory nature in only one matrix curricular and with hourly loads varying between 30h and 60h. It is evident that the teaching of PICS is still scarce in Brazil, indirectly affecting the Public Health System, since the egress profile of dental surgeons is still centered on the biomedical model, hindering policies and encouraging the use of complementary alternatives in the SUS.